संविधानवाद : लोकतांत्रिक व्यवस्था का आधारभूत तत्व: The Boundaries and Limits of Political Power in Democracy (Journal of Advances and Scholarly Researches in Allied Education, 2015)
राजसत्ता के प्रयोग की सीमाएं एवं मर्यादाएं निश्चित की जानी चाहिए